2020
DOI: 10.1002/ccd.29181
|View full text |Cite
|
Sign up to set email alerts
|

Cost savings for pVAD compared to ECMO in the management of acute myocardial infarction complicated by cardiogenic shock: An episode‐of‐care analysis

Abstract: Background Acute myocardial infarction complicated by cardiogenic shock (AMICS) occurs in up to 10% of acute myocardial infarction admissions and is associated with high mortality, frequent adverse outcomes, prolonged hospitalizations, extensive medical resource utilization, and major cost. Using hospital cost data for Medicare Fee‐for‐Service (FFS) patients with AMICS, we sought to evaluate in hospital and 45‐day outcomes and cost, comparing patients treated with percutaneous ventricular assist device (pVAD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…In our study, Impella patients were directly discharged home more often and had a shorter length of stay compared to VA‐ECMO patients. These findings have also been reported previously 14,15,30,31 . Additionally, the associated in‐hospital costs were on average lower for Impella patients compared to VA‐ECMO patients, which is also in accordance with previous literature 14,31,32 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, Impella patients were directly discharged home more often and had a shorter length of stay compared to VA‐ECMO patients. These findings have also been reported previously 14,15,30,31 . Additionally, the associated in‐hospital costs were on average lower for Impella patients compared to VA‐ECMO patients, which is also in accordance with previous literature 14,31,32 .…”
Section: Discussionsupporting
confidence: 92%
“…12 Contrary to the lack of evidence substantiating outcome improvements, it is well-known that MCS is accompanied by various adverse events and high resource demands. 13,14 The comparison of adverse event rates in AMICS patients supported by an Impella and/or VA-ECMO has been described in several small retrospective studies and only one large retrospective cohort (n = 6290) from the National Inpatient Sample (NIS) database from the United States of America (USA) between 2015 and 2017. 15 All previously published studies enrolled patients for over 5 years or were published more than 5 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the lack of an accurate scoring system for AMI patients, 4610 patients and 30 risk factors relating to AMI were selected using sample data from the MIMIC-III database [14][15][16][17][18]. Using a random forest [19] selection method identi ed 19 risk factors that had been identi ed in the multivariate logistic regression analysis [20].…”
Section: Discussionmentioning
confidence: 99%
“…This technology usually exposes patients to a variety of complications, so patients often have to pay high costs (12,13). With the discovery that antimicrobial prophylaxis in patients on ECMO could reduce nosocomial infection and showed lower mortality, some studies have found that antimicrobial prophylaxis and overuse have gradually emerged, so whether it is a cost-effective intervention is still undiscovered (14,15).…”
Section: Original Articlementioning
confidence: 99%